ATG5 counteracts nutritional stress in human hepatoblastoma HepG2 cells by regulating autophagic flux - ZHAO Lian; XIANG Dongyun; WU Huiyi (陆军军医大学学报)
Objective‍　‍To investigate the effect of nutritional deficiency on autophagic flux in human hepatoblastoma HepG2 cells and the autophagy-dependent molecular pathway mediated by ATG5 against nutritional stress. Methods‍　‍Lentiviral siRNA knockdown of ATG5 was performed to knock down the expression in HepG2 cells, and the transfection was verified by Western blotting and qRT-PCR. HBSS was used to treat HepG2 cells for 0, 1, 2, 3, 4, 5, 6 and 7 h for starvation-induced autophagy. Monodansylcadaverine (MDC) fluorescence staining was employed to detect the formation of intracellular autophagic vesicles. Western blotting was performed to measure the expression changes in microtubule-associated protein 1A/1B-light chain 3 (LC3), autophagy receptor protein (sequestosome 1, P62), autophagy-related gene 5 (ATG5) and nutrient stress pathway (AMPK/mTOR pathway) related proteins. CCK-8 assay was utilized to test cell proliferation. Results‍　‍Compared with the HepG2 cells under conventional culture medium, starvation induction resulted in more autophagic vacuoles (accumulation of autofluorescent marker, MDC), which peaked at 6 h of starvation (P<0.000 1), up-regulated protein levels of LC3B-Ⅱ and ATG5 (P<0.05), decreased protein expression of P62 (P<0.05), gradual activation of the AMPK/mTOR pathway with elapse of starvation time, and increase in the intensity of autophagic flux. However, in the HepG2 cells with ATG5 knockdown, starvation treatment led to decreased ATG5 expression, no significant difference in LC3B-II and P62 changes, inhibited autophagic flux, and suppressed cell proliferation (P<0.000 1). Conclusion‍　‍Human hepatoblastoma HepG2 cells can regulate autophagic flux to against nutritional stress by inducing ATG5 expression.